PENGARUH PEMBELANJAAN PERIKLANAN DAN PROMOSI HARGA PADA EKUITAS MEREK - Maklon Felipus Killa (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study aimed to examine the effect of perceived advertising spending and price deal on brand equity’s dimension, and the effect of brand equity’s dimension on brand equity based on consumer’s perspective. University students in Yogyakarta were taken for the sample, those who owned and used notebook. Meanwhile the purposive sampling was used for sampling technique. 350 questionnaires were distributed and 328 were used. The finding showed that brand loyalty was positively and significantly affected on brand equity, whereas perceived quality, brand awareness, and brand image were not positively and significantly affected on brand equity. Besides, perceived advertising spending was positively and significantly affected the dimension of brand equity (perceived quality, brand loyalty, brand awareness, and brand image). Price deal was negatively and significantly affected on perceived quality and brand image.